The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/jmv.28445
|View full text |Cite
|
Sign up to set email alerts
|

The salivary and nasopharyngeal microbiomes are associated with SARS‐CoV‐2 infection and disease severity

Abstract: Emerging evidence suggests the oral and upper respiratory microbiota may play important roles in modulating host immune responses to viral infection. As the host microbiome may be involved in the pathophysiology of coronavirus disease 2019 , we investigated associations between the oral and nasopharyngeal microbiome and COVID-19 severity. We collected saliva (n = 78) and nasopharyngeal swab (n = 66) samples from a COVID-19 cohort and characterized the microbiomes using 16S ribosomal RNA gene sequencing. We als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 61 publications
(144 reference statements)
3
11
0
Order By: Relevance
“…Fusobacterium periodonticum (Fp) was among the most significantly reduced species in the COVID-19 patients as compared to the false positives, in line with a nasopharyngeal microbiome case/control study ( Nardelli et al, 2021 ), with similar trends observed between the salivary and nasopharyngeal microbiome ( Kim et al, 2023 ). Nardelli et al (2021) reported that Fp can perform surface sialylation and that some sialic acid residues on the cell surface could work as additional S protein of SARS-CoV-2 receptors.…”
Section: Discussionsupporting
confidence: 63%
“…Fusobacterium periodonticum (Fp) was among the most significantly reduced species in the COVID-19 patients as compared to the false positives, in line with a nasopharyngeal microbiome case/control study ( Nardelli et al, 2021 ), with similar trends observed between the salivary and nasopharyngeal microbiome ( Kim et al, 2023 ). Nardelli et al (2021) reported that Fp can perform surface sialylation and that some sialic acid residues on the cell surface could work as additional S protein of SARS-CoV-2 receptors.…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, we chose to include only works published in the English language. Four studies assessed the upper respiratory tract [ 21 , 22 , 23 , 24 ], including samples such as saliva, throat, tongue, oral, and nasopharyngeal. Four studies examined stool samples [ 25 , 26 , 27 , 28 ], and only one study evaluated the microbiome in both the gut and URT [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whole genome sequencing methodology was applied in two studies [ 20 , 24 ]. There was a notable variation in the selection of databases used for taxonomy classification among studies, with four studies using the Greengenes database [ 21 , 22 , 23 , 25 ]; the RDP [ 22 ], SILVA v132 [ 23 ], SILVA v138 [ 21 ], and MetaPhlAn2 (V.20) [ 28 ] databases were used in only one study each ( Figure 2 ). One study did not specify the database [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, as one of the viruses infecting our respiratory tract, SARS-CoV-2 infects and contacts the nasopharyngeal cells first. It is not surprising that the salivary and nasopharyngeal microbiota was altered during SARS-CoV-2 infection, 47 , 48 such as depletion of oral Bifidobacterium , Lactobacillus , and Solobacterium , and nasopharyngeal Paracoccus , and enrichment of nasopharyngeal Proteus , Cupravidus , and Lactobacillus in severe COVID-19 patients. 47 Similar phenomena were also found in the lower respiratory tract bacterial microbiome of COVID-19 critically ill patients who were characterized with Pseudomonas alcaligenes , Clostridium hiranonis , Acinetobacter schindleri , Sphingobacterium spp., Acinetobacter spp.…”
Section: Gi Microbiome and Metabolites In Long Covidmentioning
confidence: 99%
“…It is not surprising that the salivary and nasopharyngeal microbiota was altered during SARS-CoV-2 infection, 47 , 48 such as depletion of oral Bifidobacterium , Lactobacillus , and Solobacterium , and nasopharyngeal Paracoccus , and enrichment of nasopharyngeal Proteus , Cupravidus , and Lactobacillus in severe COVID-19 patients. 47 Similar phenomena were also found in the lower respiratory tract bacterial microbiome of COVID-19 critically ill patients who were characterized with Pseudomonas alcaligenes , Clostridium hiranonis , Acinetobacter schindleri , Sphingobacterium spp., Acinetobacter spp. and Enterobacteriaceae , while control patients characterized with lung commensal bacteria Haemophilus influenzae , Veillonella dispar , Granulicatella spp., Porphyromonas spp., and Streptococcus spp.…”
Section: Gi Microbiome and Metabolites In Long Covidmentioning
confidence: 99%